Kajian Beban Harian pada Jaringan Distribusi Penyulang Jelutung - Sabila, Rani; Djufri, Umar; Dewi, Rozlinda (Universitas Batanghari Jambi, 2024)
A distribution network is a conveyor network that connects the load center substation with the customer. The distribution network functions to distribute electrical energy to customers according to the power and voltage needed. The distribution network line from the Aurduri GI Transformer Bay goes to the incoming to be lowered voltage from 150kv to 20kv. After the voltage is lowered, it is directly channeled to the Jelutung Feeder to find out the daily load on the distribution network. The population in this study is